Studies on Development of Ready-to-Serve (RTS) Beverage From Guava (Psidium gujava L.), Aonla (Emblica officinalis Gaertn.), Ginger (Zingiber officinale Roscoe) and Fennel Seed (Foeniculum vulgare Mill) - Km Anisha Singh,; Bhagwan Deen, (The Bioscan, 2025)
The Gauva( Psidium guajava L.), Aonla( Emblica officinalis Gaertn.), Ginger (Zingiber officinale Roscoe) and Fennel seeds (Foeniculum vulgare Mill) have nutritional, medicinal, and therapeutic values. The present research was conducted at the Post Graduate Laboratory of the Department of Post Harvest Management, College of Horticulture and Forestry, Acharya Narendra Deva University of Agriculture & Technology, Kumarganj, Ayodhya (U.P.) during the year 2023–2024. In the present studies, guava juice, aonla juice, ginger juice and fennel seed water extract were blended in different ratios viz., 86:5:5:4 (T1), 72:10:10:8 (T2), 58:15:15:12 (T3), 44:20:20:16 (T4), 30:25:25:20 (T5) for the preparation of RTS. Ten percent of blend comprising 86 percent guava juice, 5 percent aonla juice,5 percent ginger and 4 percent fennel seeds was found best on 9- point Hedonic Scale for the preparation of results RTS with 13 percent TSS, 0.3 percent acidity and 70 ppm So2 than other blend combinations. Ascorbic acid (vitamin C), non-reducing sugars, and organoleptic quality declined with storage period whereas TSS, acidity, reducing sugars, total sugars, and browning increased with storage period. The RTS retained its organoleptic qualities upto 3 months, In results acceptable quality of the showed that guava, aonla, ginger and fennel seed can be used to make palatable RTS that can be stored 3 months with acceptable score.